Investigation on Groundwater Quality and Treatment for Fluoride Reduction in Kaltungo, Gombe State, Nigeria - S. B. Onoja; M. O. Udochukwu; J. F. Malum (New Visions in Science and Technology Vol. 3, 2021)
The people of Kaltungo town depend on groundwater from hand dug wells and boreholes for their water needs but children who grow up in the town during the ages of teething end up having mottled teeth. It is being thought that the mottling of teeth is caused by chemical characteristics in the town’s sources of drinking water. For a period of 12 months, the physico-chemical properties of Kaltungo groundwater were determined. Odour, colour, taste, temperature, turbidity, and TDS were researched as physical qualities, whereas conductivity, pH, chloride, iron, copper, lead, zinc, fluoride, cadmium, nitrates, TH, total alkalinity (TA), and fluoride were studied as chemical characteristics. For the duration of the investigation, nine water samples were taken monthly, three from three manually dug wells and six from six boreholes. Except for temperature, which had a mean of 29.7°C, which was still within ambient temperature, the results showed that other physical parameters were within their maximum limits, except for iron and fluoride. The majority of the chemical values were below the suggested maximum levels. Iron concentrations ranged from 0.13 to 1.60 mg/l in hand dug wells and 0.07 to 2.35 mg/l in boreholes, while fluoride from hand dug wells ranged from 1.58 to 2.30 mg/l and from 1.29 to 1.90 mg/l in bore holes. Iron had mean monthly values of 0.9mg/l while had 1.66 mg/l, all are above the recommended standards for iron at 0.3mg/l and fluoride at 1.5mg/l concentrations respectively. Treatments for flouride removal was carried out using alum, bone charcoal and Moringa olifera seeds as substances that can be easily accessed and affordable. Fluoride concentrations in the water were reduced when treated with dosages greater than 10g/l of raw water by between 15% and 43% reduction. It is recommended that Kaltungo groundwater should be treated for fluoride removal before consumption to avert teeth mottling.